Sounds of protolanguages: Some preliminary insights from developmental psychology - Boero, Daniela Lenti (Theoria et Historia Scientiarum, 2015)
In present paper I examine the transition from crying to word in human infants and propose that it might be a treasure acoustic box helping us to conceive how our ancestor’s sounds might have been, and to outline breakpoints that might help us in making hypotheses about possible subsequent phases of language evolution.